2022
DOI: 10.4103/npmj.npmj_80_22
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Perception and Determinants of Delayed Presentation of Children with Severe Malaria in an Emergency Room in Benin City, Nigeria

Abstract: Introduction: Severe malaria is a leading cause of mortality due to late presentation to health facilities. Hence, there is a need to identify and mitigate factors promoting delayed presentation with severe malaria. Objective: This study aimed to evaluate determinants of delayed presentation of children with severe malaria in a tertiary referral hospital. Methods: This study adopted a descriptive, cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This nding is consistent with what previous studies [9,37,38] conducted in urban communities in Nigeria have reported. Therefore, a combination of approaches and strategies when designing, implementing and evaluating interventions targeting encouraging of seeking of proper or appropriate care for suspected malaria infection will be desirable.…”
Section: Discussionsupporting
confidence: 93%
“…This nding is consistent with what previous studies [9,37,38] conducted in urban communities in Nigeria have reported. Therefore, a combination of approaches and strategies when designing, implementing and evaluating interventions targeting encouraging of seeking of proper or appropriate care for suspected malaria infection will be desirable.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, poor health-seeking behavior, such as delayed presentation to health facilities and self-treatment at home, is prevalent in our environment. 5,27,29 In our setting, this is a significant contributor to childhood morbidity and mortality. 30,31 Our primary health care system's limited functionality also impedes timely access to health facilities, as does indiscriminate access to prescription drugs in chemist stores, supermarkets, and sometimes from hawkers.…”
Section: Discussionmentioning
confidence: 97%
“…Regular training of clinical staff can be life-saving in our medically-underserved region where delayed presentation and suboptimal interventions in health facilities contribute to poor outcome of paediatric emergencies. [27,28] Nonetheless, our participants desired the opportunity to undergo long-term critical care training including clinical rotations in intensive care units which has been found to be beneficial to paediatric residents in other settings. [29,30] Participants' baseline understanding of respiratory support equipment and patient interfaces was low, consistent with earlier reports of shortages of critical care resources in (LMICs.…”
Section: Discussionmentioning
confidence: 99%